Penning spectroscopy and structure of acetylene oligomers in He nanodroplets. Issue 18 (29th April 2020) - Mandal, S.; Gopal, R.; Shcherbinin, M.; D'Elia, A.; Srinivas, H.; Richter, R.; Coreno, M.; Bapat, B.; Mudrich, M.; Krishnan, S. R.; Sharma, V.
Abstract : Penning spectroscopy of acetylene molecules dissolved in superfluid He nanodroplets reveals the loosely held molecular aggregate collapsing into a covalently bound oligomer ion upon indirect ionization effected by the photoexcited He* in the host. Abstract : Embedded atoms or molecules in a photoexcited He nanodroplet are well-known to be ionized through inter-atomic relaxation in a Penning process. In this work, we investigate the Penning ionization of acetylene oligomers occurring from the photoexcitation bands of He nanodroplets. In close analogy to conventional Penning electron spectroscopy by thermal atomic collisions, the n = 2 photoexcitation band plays the role of the metastable atomic 1s2s 3, 1 S He*. This facilitates electron spectroscopy of acetylene aggregates in the sub-Kelvin He environment, providing the following insight into their structure: the molecules in the dopant cluster are loosely bound van der Waals complexes rather than forming covalent compounds. In addition, this work reveals a Penning process stemming from the n = 4 band where charge-transfer from autoionized He in the droplets is known to be the dominant relaxation channel. This allows for excited states of the remnant dopant oligomer Penning-ions to be studied. Hence, we demonstrate Penning ionization electron spectroscopy of doped droplets as an effective technique for investigating dopant oligomers which are easily formed by attachment to the host cluster.